Tolu Dance in The Senggighilang Art Studio, Bailang Village, Bunaken District, Manado City - Apriliani Marsella Debora Moray; Kompiang Gede Widyana; Suminto (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2025)
Higher education in Indonesia aims to produce quality graduates through the Merdeka Belajar Kampus Merdeka program, but the implementation of this program still faces a number of challenges, especially in the lack of dance literacy, especially in North Sulawesi. This study aims to analyze the elements and symbolic meanings contained in the Tolu dance performance: Our Appreciation for You at the Senggighilang Art Studio. This study uses a qualitative descriptive approach, with aesthetic theory and semiotic theory dance literacy, especially in North Sulawesi. This study aims to analyze the elements and symbolic meanings containedin the Tolu dance performance: Our Appreciation for You at the Senggighilang Art Studio. This study uses a qualitativedescriptive approach, with aesthetic theory and semiotic theory.The data collection process goes through the stages of observation, interviews, documentation and data